Design estratégico, intêligencia emocional e a criança: aplicando o design positivo na compreensão das emoções desde a infância - Menegussi, Nicolli (Universidade do Vale do Rio dos Sinos, 2021)
Emotions are presented innately and universally in individuals. Experiencing them is at the heart of the human being. Playing a decisive role with regard to a healthy emotional and psychic development, especially in preschool age, when the individual is forming his identity, personality and individuality. For this to occur, it is necessary to understand and communicate the emotions themselves, entitled emotional intelligence. The present work aimed to investigate the universe of emotions, especially with regard to its diagnosis in childhood, in order to explore the possibilities of strategic design in this theme. Given the complexity of the scenario envisaged, we chose to use the Metaprojetual approach, given the conditions that such methodology offers to gather, identify and analyze the information obtained, and thus to make up a broad knowledge of the project problem. Based on the research esplanade, it is suggested that the best way to present the chosen research object is to insert it in the child's reality, in an analog and interactive way. For this, we used the tools of active learning and positive design to enable the execution of child autonomy, combined with motor and cognitive exploration when developing the emotional intelligence of the little ones.
Keywords: Design estratégico; Design editorial; Design emocional; Emoções; Psicologia infantil; Strategic design; Editorial design; Emotional design; Emotions; Child psychology